Hubungan Dukungan Keluarga dengan Tingkat Kecemasan Ibu dalam Menghadapi Kehamilan Trimester III - Niza ardiyanti; Zaini, Mad; Suryaningsih, Yeni (Jurnal Pustaka Keperawatan (Pusat Akses kajian Keperawatan), 2025)
Anxiety is a common emotional response experienced by pregnant women during the third trimester, characterised by feelings of discomfort, worry, and tension that are difficult to control. Data from the East Java Provincial Health Office (2022) showed that 52.3% of 679,765 pregnant women reported experiencing anxiety, while a study conducted in Jember Regency reported a prevalence of up to 90%. Family support is believed to be an important external factor associated with reduced anxiety among pregnant women. This study aimed to analyse the relationship between family support and anxiety levels among women in the third trimester of pregnancy. This study employed an analytical survey design with a cross-sectional approach. The population consisted of all third-trimester pregnant women in the working area of Pakusari Public Health Centre, totalling 100 women. A total of 100 respondents from four villages were selected using cluster purposive sampling. Family support was measured using the 20-item Family Support Pregnancy Questionnaire (FSPQ), while anxiety levels were assessed using the 10-item Pregnancy-Related Anxiety Questionnaire-Revised 2 (PRAQ-R2). Data were analysed using Spearman’s rank correlation test. Most respondents (94.0%) received a good level of family support, while more than half (54.0%) experienced moderate anxiety. The Spearman’s rank correlation test showed a statistically significant negative relationship between family support and anxiety levels (p = 0.039; r = ?0.207). There was a statistically significant negative relationship between family support and anxiety levels among women in the third trimester of pregnancy. Higher levels of family support were associated with lower levels of maternal anxiety. Healthcare professionals are encouraged to actively involve family members in antenatal care services to help reduce anxiety among pregnant women